رشوة الخبير الطبي القضائي (دراسة مقارنة) - سلخ, محمد لمين; حويذق, عثمان (جامعة الوادي university of eloued, 2022)
ملخص تعتبر جريمة الرشوة من أخطر جرائم الفساد، وتزيد خطورتها عند ارتكابها من طرف خبير طبي قضائي، نظرا لتأثيره على قرارات العدالة وحقوق الأطراف وعلى المجتمع ككل، بالمقابل نجد المشرع يعاقب عليها كما لو أنها جريمة رشوة عادية، بينما ينبغي أن يتم النص عليها بشكل خاص، أو تشديد العقوبة المقررة لمرتكبها إذا كان خبير قضائي، هذا ما ندعو إليه بعد الدراسة هذه الجريمة، والتطرق لأركانها والعقوبة المقررة لمرتكبها. Abstract: Bribery is considered one of the most serious crimes of corruption. It is even more serious when committed by a medico-legal expert, because of its impact on the decisions of justice and the rights of the parties and on society. Despite that, this crime is penalized as if it is an ordinary crime of bribery, while it should be particularly legislated or get its penalty seriously increased especially if the defendant is a legal expert. And this is what we call for after studying this crime and addressing its elements and penalty
Bribery Of The Medico-legal Expert (a Comparative Study
مقال
Keywords: رشوة ; خبير قضائي ; خبير طبي ; مسؤولية جزائية ; قانون الوقاية من الفساد; Bribe ; legal expert ; medical expert ; Criminal liability ; Corruption Prevention Law